Perbedaan Pola Spektrum Frekuensi Suara Pengucapan Daftar Tutur Kata Bahasa Indonesia pada Anak dengan Geligi Protrusif (Kajian pada Anak Laki-Laki Umur 9 dan 12 Tahun) - Rinaldi Budi Utomo (Faculty of Dentistry, Universitas Gadjah Mada, 2015)
Difference of Sound Frequency Spectrum Pattern of Pronunciation of Indonesian Speech List in Children with Protrusive Teeth (In 9-12 Year Old Male Children). Clarity of pronouncations for early detection of oral disorders in children has been standardized into an Indonesian speech list that is popularly spoken by primary school children, but it requires a clinical application to be used as a speech test tool lists. The purpose of this study is that the standardized Indonesian speech list can be applied clinically in the case of Angle Class I malocclusion with protrusive anterior teeth in male children aged 9 and 12 years. The list is expected to be used as a test tool for speech disorders by looking at the spectrum patterns of speech sound frequency using Readability Meter tool. The arrangement of Indonesian speech list that is popular at children in school age is a contribution to the development of early detection of cavum oris abnormalities that occur in children to ease and accelerate the determination of diagnosis. This study was conducted using analytical epidemiological method with cross sectional design; the subjects were observed one time. The subjects were 24 male children from Javanese ethnic; 12 of there were 9 years old and the other 12 were 12 years old with protrusive anterior teeth and overjet 3-4 mm. Both of the groups pronounced the Indonesian speech list containing the dominant sound frequency in malocclusion Angle class I protrusive variation in the form of words /bakteri/, /demokrasi/, /formulir/, /konveksi/, /limbah/, /nasional/, /ringkas/, /samudera/, /takjub/, /ventilasi/. The recording was directly conducted in a soundproof room through sound recorder program using flat microphones and sound processing mixer. Then, the dominant sound frequency (Hz) and the display of the spectrum patterns of the sound frequency was measured using Cool Edit Pro 2.0 and Excel software. An Excel analysis shows highly significant differences between male children aged 9 years and 12 years in Angle Class I malocclusion with protrusive variations in speech of 10 Indonesian words with the coefficient of determination “R” in the equation chart of spectrum patterns of sound frequency. Male children aged 9 years have a spectrum pattern of sound frequency which is lower and flatter than those aged 12 years.